Legal and Organizational Measures of Counteraction Against Corruption Правовые и организационные мероприятия противодействия коррупции - Dorovskoy V. A. (Problemi Ekonomiki, 2010)
The article assessed the level of corruption in Ukraine. Stages of anti-corruption legislation in Ukraine is investigated. Recommendations for improving the organization of anti-corruption activities in the country and bring the system of anti-corruption legislation to international standards. В статье проведена оценка уровня коррупции в Украине. Исследованы этапы формирования антикоррупционного законодательства в Украине. Представлены рекомендации по совершенствованию организации антикоррупционной деятельности в стране и приведению системы антикоррупционного законодательства в соответствии с международными стандартами.